The Financing sustainability of a family social communication media business (newpapers) from Lara state (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
The purpose of this research was to assess the financial sustainability of a family business of social communication media (newspapers) from Lara State. The criteria for defining enterprises as family is based on the ownership and management which are carried out by a family group, since these important organizations highly contribute to the development of global and local economy, highlighting as specific objective recommending guidelines to allow financial sustainability for these companies over time. Research corresponded to a descriptive research with a field design. The sample consisted of six daily state movements, which answered a questionnaire with 44 open and closed questions, in order to measure the variable under study, analyzing the data using descriptive statistics with graphics that reflect the results. We conclude that these companies must develop financial analysis mechanisms that allow them set a comprehensive judgment on the reality of the company when making decisions, beyond the view of organizational and family leader, it is still advisable to formalize internal processes and external experts participation, along with a design and development of strategic planning, budget planning, management control systems and succession planning supported by well information system.
Keywords: financial sustainability; family businesses; model of the five circles